Application of association rules to ball possessions in professional men’s football - Maneiro, Rubén; Amatria, Mario; Losada, José L.; Jonsson, Gudberg K.; Ardá, Antonio; Iván-Baragaño, Iyán (Frontiers in Psychology, 2025)
IntroductionThis study represents one of the first attempts to apply association rule mining to the analysis of ball possession in professional men’s football. The goal was to uncover hidden patterns among key tactical variables influencing possession success.MethodsUsing observational methodology, 2,324 ball possessions from the UEFA Euro 2020 championship were analyzed. The Apriori algorithm was applied to generate a total of 4,818 association rules, focusing on variables such as possession time, tactical intent, and field zones where possession occurred.ResultsThe results show that short possessions, with the intent to progress and developed in advanced zones of the field, are strongly associated with successful outcomes. This is reflected in high lift values (up to 40) and strong confidence levels. In contrast, long possessions in offensive zones did not consistently correlate with success.DiscussionThese findings suggest that possession duration alone is not a reliable predictor of success. Instead, the combination of short possessions, in advanced zones, and with progressive intent, is more closely associated with positive outcomes. Association rule mining emerges as a valid and interpretable tool to support decision-making in elite football.